Model Blended Learning & Hybrid Learning Untuk Keberhasilan Transformasi Digital Menuju Smart Society - Susi Yunarti; Wijayanti Wijayanti; Dian Harmaningsih (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
The purpose and objective of this research is to find out and explain the application of blended learningmodels and hybrid learning methods in universities as an effort to help realize digital transformationtowards a smart society. To answer the problem of the readiness of human resources, who shouldprepare them, and how to prepare them, so that the digital transformation process can run as desiredtogether. A qualitative descriptive analysis has been carried out based on CMC cyberspace theory,digital transformation and the concepts of blended learning and hybrid learning. to explain the resultsof observations and interviews with lecturers from 4 state universities and 30 students from 2 privateuniversities in Jakarta, online during the even semester 2021 lectures. The results reveal that the onlinelecture process is not fully reliable for realizing digital transformation, but rather a system that is ableto combine (Blended) all teaching methods both offline and online (hybrid) in the learning process inhigher education. And for its implementation, it requires high integrity, dedication and self-motivationfrom both students and lecturers. Research data shows that 35% of students are quite excited to doonline learning, but 65% of students have become bored. And when asked to choose, 70% of studentsstill want offline learning. Conclusion The success of digital literacy in society starting from universitiesthrough the application of blended learning models and hybrid learning methods is an indicator of therunning of the digital transformation process which is expected to lead to the development of thecommunity's ability to adapt and become part of a smart society civilization